The problems faced by teachers in institutes of teaching Arabic to non-native speakers from their point of view ((Study in institutes of teaching Arabic for non-native speakers in Damascus)) - Rahma, Aziza; Al-Esh, Mahdi; Hussein , Zainab (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The study aimed to identify the problems faced by teachers of Arabic language in the institutes of teaching Arabic language to non-native speakers during their work, and to investigate the impact of both gender variables and years of experience in the degree of appreciation of these problems by applying a questionnaire consisting of (24) The results of the study showed that the estimates of the teachers of the Arabic language (Arabic, Arabic, English, Arabic, English, Arabic, and Arabic) (2.58), and their assessment of the linguistic problems they face while performing their work came to a medium degree with a mean average of 1.54, and their assessment of the problems encountered during the course of their work was high and with an average of (2.06). The results of the study did not show the effect of sex variables and years of experience in the estimates of Arabic language teachers on the problems they face while doing their work.